CRITICAL REVIEW OF THE RELEVANCE OF MULTI-CONTRACT FINANCING OF QARDLU BI SYARTI RAHNI TO FIQIH MUAMALAH - Faisal, Akbar Hamdani Dwi; Nuha, Ulin (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
The purpose of this study was to determine how the implementation, suitability, and challenges and obstacles of qardlu bi syarti rahni products at BMT Ummat Sejahtera Abadi Jepara are based on the perspective of muamalah fiqh. The type of research used in this study is field research with a descriptive qualitative approach. Data collection techniques in this study were through observation, interviews, and documentation. Then the data was analyzed through several stages, namely data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the study related to the suitability of multi qardlu bi syarti rahni contracts to muamalah fiqh, namely, in terms of the contract, it is appropriate. The combination of qard and rahn contracts is combining contracts that are still the same type, namely the tabarru' contract. On the other hand, in the book al-uqud al-maaliyah al-murakkbah by Abdullah Imrani, the combination of these contracts is a type of mutaqabilah contract (conditional contract). Therefore, by combining contracts that are still of the same type and do not cause ambiguity, the multi-contract qardlu bi syarti rahni is in accordance with the rules of fiqh al ashlu fil muamalah al ibahah. The DSN MUI fatwa also allows rahn only for debts (al-dain) caused by qardh.